PENGARUH KUALITAS PELAYANAN KESEHATAN GIGI DAN MULUT TERHADAP KEPUASAN PASIEN BPJS DI LAYANAN PRIMER BANJARMASIN - Aulia, Ridha; Adhani, Rosihan; Taufiqurrahman, Irham; Hatta, Isnur (Dentino, 2017)
ABSTRACK Background: The patient satisfaction is an important thing that should be reached by every health facillty. As a spearhead of health service in National HealthF Insurance (JKN) era, public health center and dental practice were told to given a health service that coRuld be completed the patient satisfaction. BPJS health program is one of the effort to equalization of health standard for a whole Indonesian folk. It needed a good cooperation between the service provider and receiver to reaching the maximum of patient satisfaction. Purpose: To know the effect of oral health service quality to BPJS patient satisfaction in Banjarmasin primary service. Method: It used an observational analytic study with cross sectional design and the sample amounted to 400 patient consecutive sampling method. Analizing data were using product moment pearson correlation, simple linear regression and multiple linear regression. Result : The research showed that oral health service quality consisting of tangible, realiability, responsiveness, assurance and emphaty dimension had significant effect for patient (p<0,05). Conclusion : Thereâs a significant effect of oral health service quality to BPJS patient satisfaction in Banjarmasin primary service. Responsiveness dimension had dominant and very intense each order to patient satisfaction. A better service quality will increasing the patient satisfaction. The patient more satisfied in receiving a service can motivated them for revisit and reused the health service. Keywords: service quality, patient satisfaction, BPJS health